The influence of smoking on male reproductive parameters in a group of Iraqi subfertile men - Harmoosh, Shaimaa K.; Al Madfai, Zaid A. (Journal of the Faculty of Medicine Baghdad, 2012)
Background: Among different air pollutants, cigarette smoke contains toxic chemicals, mutagenic and carcinogenic compounds, which can adversely affect male fertility. In this study, semen parameters and reproductive hormonal concentrations of subfertile smokers were compared with subfertile non-smokers. Objectives: evaluation of the effect of cigarette smoking on male fertility by evaluating several semen parameters as well as some reproductive hormones in a group of smoker and non smokersubfertile Iraqi subjects. Patients and Methods: At the male infertility clinic of Al-yarmuk teaching hospital, Almustanseria medical college, Baghdad, Iraq from the 1st of October 2010 to the end of June 2011, 88 men (49 non-smokers, and 39 smokers) with history of subfertility for at least 1 year were evaluated by medical history, physical examination, semen analyses and reproductive hormonal profile. Results:There was a significant impairment of semen parameters namely sperm count, sperm motility and normal sperm morphology in subfertile smokers (means ± SD were 23±28.01, 11.25±16.96 and 35.41±26.44 respectively as compared to subfertilenon smokers in which means ± SD were 53.67±22.16, 27.04±15.70, 52.04±17.90 respectively and P values were < 0.005 for the 3 parameters with a non significant changes in reproductive hormonal profile between smokers and non smokers. Conclusion: Smoking does affect conventional semen parameters namely sperm count, motility and morphology significantlywith mild non significantchanges in male reproductive hormonal analysis.